Monitoring cognitive resilience in military personnel in extreme operational environments: The role of smart technologies and nutritional strategies—A scoping review protocol - Rodica Siminiuc; Dinu Turcanu (PLoS ONE, 2025)
Introduction Maintaining cognitive performance in extreme operational environments is essential for military personnel efficiency. Exposure to multiple stressors, including sleep deprivation, intense physical exertion, and limited access to food resources, can affect cognitive function and decision-making ability. Although studies on military nutrition and smart technologies exist, an integrated synthesis that analyzes their interactions is currently lacking. Materials and methods This scoping review follows the JBI methodology, with a structured study selection and data synthesis process. The analysis includes international databases and grey literature, with results presented both narratively and in tabular form, Objectives This scoping review aims to map and analyze the literature on smart technologies used for monitoring the cognitive resilience of military personnel deployed in extreme operational environments, as well as the role of nutritional strategies in supporting cognitive resilience, following the PCC criteria. Inclusion criteria Studies published after 2000 that investigated nutritional strategies and the use of smart technologies to monitor or support the cognitive resilience of military personnel will be included. Research focusing solely on physical performance or pharmacological interventions unrelated to operational nutrition was excluded, Registration This scoping review protocol was registered in the OSF (Open Science Framework): [https://doi.org/10.17605/OSF.IO/EC7MG].